Advice and behavior in intergenerational: Ultimatum games: An experimental approach - Andrew Schotter; Barry Sopher (Rutgers University, Department of Economics, 2000)
In the real world, when people play games, they often receive advice from those that have played it before them. Such advice can facilitate the creation of a convention of behavior. This paper studies the impact of advice on the behavior subjects who engage in a non-overlapping generational Ultimatum game where after a subject plays he is replaced by another subject to whom he can offer advice. Our results document the fact that allowing advice has a dramatic impact on the behavior of subjects. It diminishes the variance of offers made over time, lowers their mean, and causes Receivers to reject low offers with higher probability. In addition, by reading the advice offered we conclude that arguments of fairness are rarely used to justify the offers of Senders but are relied upon to justify rejections by Receivers.
Keywords: C91; C72; 330; conventions; culture; experimental games; intergenerational games